Case Report: GPi DBS for Non-parkinsonian Midline Tremor: A Normative Connectomic Comparison to a Failed Thalamic DBS - Morishita, Takashi; Sakai, Yuki; Mishima, Takayasu; Umemoto, George; Okun, Michael S.; Tanaka, Saori C.; Tsuboi, Yoshio; Inoue, Tooru (Frontiers in Human Neuroscience, 2021)
Introduction: The clinical efficacy of deep brain stimulation (DBS) for midline tremor has been heterogenous. Here, we present an atypical case with facial and palatal tremor treated with DBS. We aimed to show the difference between the fibers affected by stimulation of the two targets (globus pallidus interna (GPi) and ventral intermediate (Vim) thalamic nucleus) using a normative connectome analysis. Case Report: A 76-year-old woman with a four-year history of severe facial and palatal tremor due to craniofacial dystonia. Following a failed bilateral Vim DBS, explantation of preexisting leads and implantation of bilateral GPi leads resulted in the resolution of tremor symptoms following a failed bilateral Vim DBS. We performed a normalized connectome analysis using the volume of tissue activated (VTA) as a region of interest. The results revealed that the fiber tracts associated with VTA of GPi DBS had connections with the facial area of the motor cortex while the Vim DBS did not. Conclusion: This case study suggests the possibility that GPi DBS may be considered for midline tremor, and that the normative connectome analysis may possibly offer clues as to the structures underpinning a positive response. We may refine targets for some of the more difficult to control symptoms such as the midline tremor in this case.